2004
DOI: 10.1208/pt050112
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and physicochemical characterization of 5 niclosamide solvates and 1 hemisolvate

Abstract: The purpose of the study was to characterize the physicochemical, structural, and spectral properties of the 1:1 niclosamide and methanol, diethyl ether, dimethyl sulfoxide, N,N' dimethylformamide, and tetrahydrofuran solvates and the 2:1 niclosamide and tetraethylene glycol hemisolvate prepared by recrystallization from these organic solvents. Structural, spectral, and thermal analysis results confirmed the presence of the solvents and differences in the structural properties of these solvates. In addition, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 7 publications
(2 reference statements)
3
31
0
Order By: Relevance
“…The relationship between the two niclosamide monohydrates was studied further by a range of methods, which consistently suggest that H A is the kinetically favoured form which readily transforms into H B . (Manek & Kolling, 2004, Tian et al, 2010, van Tonder, Mahlatji, et al, 2004 Physical property measurements reported on the solvates listed above, including solubility, dissolution and thermal properties, revealed a high affinity for water of all these crystal forms. (van Tonder, Mahlatji, et al, 2004, van Tonder, Maleka, et al, 2004 This may have potentially impacted some of the measurements reported, given that, for example, niclosamide tetrahydrofuran solvate crystals are reported to undergo desolvation within minutes of being removed from the mother liquor.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between the two niclosamide monohydrates was studied further by a range of methods, which consistently suggest that H A is the kinetically favoured form which readily transforms into H B . (Manek & Kolling, 2004, Tian et al, 2010, van Tonder, Mahlatji, et al, 2004 Physical property measurements reported on the solvates listed above, including solubility, dissolution and thermal properties, revealed a high affinity for water of all these crystal forms. (van Tonder, Mahlatji, et al, 2004, van Tonder, Maleka, et al, 2004 This may have potentially impacted some of the measurements reported, given that, for example, niclosamide tetrahydrofuran solvate crystals are reported to undergo desolvation within minutes of being removed from the mother liquor.…”
Section: Figurementioning
confidence: 99%
“…(Manek & Kolling, 2004, Tian et al, 2010, van Tonder, Mahlatji, et al, 2004 Physical property measurements reported on the solvates listed above, including solubility, dissolution and thermal properties, revealed a high affinity for water of all these crystal forms. (van Tonder, Mahlatji, et al, 2004, van Tonder, Maleka, et al, 2004 This may have potentially impacted some of the measurements reported, given that, for example, niclosamide tetrahydrofuran solvate crystals are reported to undergo desolvation within minutes of being removed from the mother liquor. (Caira et al, 1998) For the three niclosamide crystal forms with known crystals structures, the different modes of solvent inclusion observed correlate well with the desolvation properties observed.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The H-bonding patterns and the topology of methanol molecule inclusion (from single crystal XRD) led to the prediction that considerable energy would be required to eliminate the toxic solvent from the crystal. Non-isothermal reaction kinetics by TGA vindicated the single crystal XRD findings, as the desolvation activation energy was quantified as 148.7±9.3 kJ/mol, which is considerably higher than values reported previously for other methanol solvates (36,37).…”
Section: Resultsmentioning
confidence: 42%
“…Thermodynamic stability VTXRPD (Figure 8) confirmed that the desolvation of Pyr-MeOH led to crystal collapse and concurrent recrystallization into Pyr. The activation energy required for the desolvation of Pyr-MeOH (148.7 ± 9.3 kJ/mol) is high in comparison with other known methanol solvates (36,37). The high activation energy required for desolvation is supported by the single crystal data of Pyr-MeOH which found the specific topology of solvent inclusion ( Figure 13) to confer additional stability on the solvated crystal structure and indicated that the collapse of this phase would require considerable energy.…”
Section: Structure Elucidationmentioning
confidence: 74%